Iniciação docente na educação infantil: cenários de uma cultura profissional - Marinho, Joselidia de Oliveira (2014)
This paper focalizes the initial teacher socialization in the Infantile Education from the acknowledgement about that as a phase of a professional life cycle on distinguish of other steps in the teachers’ carrier. It is based on the studies of sociological and anthropological mark with the comprehension that the professional reality is equally constructed by daily practices of social interactions in the work environment. It aims understanding how the initial process of professional culture building of beginners in the infantile education occurs under a view toward to the organizational and dynamics aspects of the teacher activity (events, interactions, practices, wisdoms, tensions and dilemmas). This investigation assuming the orientations of an ethnographic type approach has been developed in a Municipal Center of Infantile Education (Centro Municipal de Educação Infantil) in the city of Natal, with daycare and pre-school. The participant subjects are four female teachers with less than five years in Infantile Education career. It has used a participant observation and a semi-structured interview in the data building that had interpreted through a content analysis and sources triangulation. It delineates three dimensions to the professional culture scenarios: the personal and formative profile of the subjects, the school daily and the teacher work management. The multiform character of the finds evidences that the professional culture of the novice teachers has been constituted from the confrontation with different situations of unpredictably in their emotions, routines and pedagogical and administrative difficulties, simultaneously to the dilemmas of child care and educate. The solitude feeling has been generating from the institutional and scholar organization, which offers no material and pedagogical conditions to the peers collaboration and discussion. Finally it means that teaching in the Infantile Education must been based on an expanding network relations, been indispensable to the beginners the support and orientation related to doubts, wistfulness and expectations as means of socializing and redefining their teaching practice